Vascularized composite autograft for adult laryngotracheal stenosis and reconstruction. Issue 2 (20th June 2015) - Rich, Jason T.; Goldstein, David; Haerle, Stephan K.; Busato, Gian‐Marco; Gullane, Patrick J.; Gilbert, Ralph W.
Abstract: Background: Adult laryngotracheal reconstruction for airway stenosis and after oncologic ablation can be extremely challenging. Methods: Patients with the above conditions not amenable to or refractory to conventional treatments were offered specialized reconstruction by wrapping a contoured costal cartilage graft with a vascularized microvascular carrier. All constructs were lined with buccal mucosa grafts. Decannulation rates, quality of life questionnaires, and pulmonary function tests were performed and analyzed. Results: Eleven patients underwent this procedure, 6 for stenosis and 5 for laryngotracheal oncologic defects. Ten patients were successfully decannulated after the procedure (91%). Median time to decannulation was 4 months. At mean follow‐up of 76 months, all evaluated patients had a serviceable voice, tolerated a normal diet, and had minimal subjective shortness of breath. Conclusion: Vascularized composite autograft can be successfully used to treat severe subglottic stenosis or reconstruct large laryngotracheal defects not amenable to or refractory to conventional treatments. © 2014 Wiley Periodicals, Inc. Head Neck 38: 253–259, 2016